Arrangement of Beauty in the Sweembath Tourism Environment to Achieve Community Welfare - Farida, Farida Ariani; Tugiman, Tugiman; Hariadi , Hariadi Susilo; Dardanila, Dardanila; Saib , Saib Suwilo; Tulus, Tulus; Eva, Eva Sartini Bayu; Ma'ruf, Ma'ruf Tafsin; Amlys, Amlys Syahputra Silalahi (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2020)
Repair and construction of facilities and infrastructure for the tourist area of ​​the Sweembath is aimed at increasing the attractiveness of tourists who will visit. This is one of the physical perceptions of what facilities there are in these attractions. Perceptions of the physical function of adequate beauty arrangement, such as the function of facilities and infrastructure, self-power (motivation) of the environment which are factors in tourism development to realize social welfare. Arrangement of beauty in the environment in the tourist area of ​​the sweembath by Binaan Simalungun Village, USU's LPPM, namely (1) installing ceramics along the edge of the pool, (2) painting bridges, (3) making slides and speedboats (4) Installation of life guard chairs ), (4) painting of the outer wall at the entrance to the sweembath, (5) replacing the barrier zinc, (6) the place of purchase and ticket cutting. Improvements and making arrangements for beauty facilities form an impact in the form of responses from collective or individual subjects, such as 1) the presence of visitors who take advantage of the facilities, 2) parking attendants who regulate vehicle parking 3) merchants who sell types of merchandise, 3) Rental of premises, mats, life jackets and changing rooms. The arrangement of this beauty, affects the increase in the welfare of the community, managers and traders in the Sweembath environment.